The Relationship Between Socioeconomic Status and Nutritional Status Among Public Health Students Class of 2022 - Radhiya Dzakira, Tsabita; Wahyu Ramadhani, Reza; Izzani Muhammad, Maghfir; Juarisela, Juarisela; Naia Natasya, Adinda; Lasari, Aramika; Nurwahyuni, Linda; Warma Sari, Mila; Dhea Rahda Della, Andi; Muftadiin , Fatimatul (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Nutritional status measured using the IMT indicator (can be undernourished, normal, or overnourished) is a health condition that is influenced by the balance of nutrients in the body, where this condition can be influenced by a person's socioeconomic status which includes pocket money, family income, number of families, and expenditure on food. Objective : The aim is to determine the relationship between socioeconomic status and the nutritional status of students in the Class of 2022 at the Faculty of Public Health, Mulawarman University, Samarinda. Research Methods/ Implementation Methods : This research was conducted from October 28 to November 1, 2024, at the Anthropometry Laboratory, Faculty of Public Health, Mulawarman University. The target of this study were 60 students of class 2022 from the Faculty of Public Health, Mulawarman University. The research design used is a Cross-Sectional design with a quantitative approach. Results : From the Asymptotic Significance (2-sided) value obtained, there is no relationship between pocket money and the nutritional status of students (p=0.252). There is no relationship between family income and the nutritional status of students (p=0.720). There is no relationship between number of families and the nutritional status of students (p=0.620). There is no relationship between food expenditure and the nutritional status of students (p=0.125). Conclusion/Lesson Learned : There is no relationship between socioeconomic status, namely pocket money, family income, number of families, and expenditure on food on the nutritional status of 2022 students of the Faculty of Public Health, Mulawarman University.